The impact of social media live streaming on fashion brands’ sales performance: A case study of TikTok - Yuan, Meng (International Scientific Technical and Economic Research, 2025)
With the rapid development of mobile internet and social media, livestreaming sales have become a crucial channel for fashion brands to expand their markets and boost sales performance. Douyin and TikTok, with their vast user bases and sophisticated content distribution mechanisms, have become core platforms for livestreaming e-commerce. This paper, focusing on the impact of livestreaming sales on the sales performance of fashion brands, systematically analyzes the operational models, impact mechanisms, and pathways of livestreaming sales, drawing on case studies of fast fashion and luxury brands for comparative study. The study finds that livestreaming sales forms a complete conversion cycle through "traffic acquisition, trust building, and consumer stimulation," effectively driving brand exposure and sales. Furthermore, livestreaming strategies vary significantly across fashion brands: fast fashion brands prioritize traffic volume and price advantages, luxury brands emphasize brand storytelling and high-end experiences, and emerging brands rely on differentiation and emotional resonance to achieve breakthroughs. The paper also points out that while livestreaming sales presents significant opportunities, it also carries potential risks, such as reliance on low prices, brand image dilution, and operational pressure. Based on the research findings, this paper proposes management recommendations, including optimizing brand strategies, improving platform mechanisms, and forecasting future trends. Overall, live streaming sales on social media is not only a new e-commerce model, but also a strategic location for fashion brands in the process of digital transformation. It is of great significance to both short-term sales and long-term brand value.